Potential Trade-Offs Between Nature-Based Tourism and Forestry, a Case Study in Northern Finland - Anssi Ahtikoski; Seija Tuulentie; Ville Hallikainen; Vesa Nivala; Eero Vatanen; Liisa Tyrväinen; Hannu Salminen (Forests, 2011)
Forestry, as a large industry, has significant impacts on the quality of nature-based tourism landscapes in boreal forests. In Finland, the rapid growth of nature-based tourism has expanded outdoor recreation activities from protected areas into timber production forests; this is particularly so in northern Finland. This paper focuses on assessing balanced local net impacts of three alternative land-use scenarios, in which the level of integration between nature-based tourism (NBT) and traditional forestry is varied. The study is located in northern Finland in the area between two top-rated tourist resorts, Ylläs and Levi. The results of the case study support the idea of an eligible integration between NBT and forestry, which takes into account scenic qualities of forested landscapes by restricting traditional management practices. In our case, the increased number of tourists (due to a more attractive forest environment) offset the losses accrued in forestry (due to restricted forest management).